2017
DOI: 10.1159/000480458
|View full text |Cite
|
Sign up to set email alerts
|

Dual Diagnosis of Ellis-van Creveld Syndrome and Hearing Loss in a Consanguineous Family

Abstract: Multilocus analysis of rare or genetically heterogeneous diseases is a distinct advantage of next-generation sequencing (NGS) over conventional single-gene investigations. Recent studies have begun to uncover an under-recognized prevalence of dual molecular diagnoses in patients with a “blended” phenotype that is the result of 2 clinical diagnoses involving 2 separate genetic loci. This blended phenotype could be mistakenly interpreted as a novel clinical extension of a single-gene disorder. In this study, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…Accessed Aug 2020), and these were related to non-syndromic autosomal recessive hearing loss.Consistent with the recessive inheritance, 10 possible causative variants in 3 deafness-related genes (MYO15A, COL11A2, and CDH23) were detected in homozygotes (two families) or compound heterozygotes (four families, Additional le 1). Although the genes previously known to be associated with hearing loss, except for 3 variants (p.T323Hfs*19 in COL11A2, p.3417delS and c.5964+3G>A in the MYO15A gene) associated with non-syndromic deafness in previous studies[17][18][19][20][21], 7/10 variants were identi ed in this study for the rst time; these included 4 missense variants (p.C1297F and p.K2217E in CDH23, p.G1315R and p.F2861S in MYO15A), 2 frame-shifting (p.Q2749Efs*93 and p.S3474Pfs*43 in MYO15A), and 1 splicing site (c.4875+1G>T in MYO15A). Moreover, c.4875+1G>T at the conserved donor splice site of MYO15A might affect the correct translation of the protein.…”
mentioning
confidence: 97%
“…Accessed Aug 2020), and these were related to non-syndromic autosomal recessive hearing loss.Consistent with the recessive inheritance, 10 possible causative variants in 3 deafness-related genes (MYO15A, COL11A2, and CDH23) were detected in homozygotes (two families) or compound heterozygotes (four families, Additional le 1). Although the genes previously known to be associated with hearing loss, except for 3 variants (p.T323Hfs*19 in COL11A2, p.3417delS and c.5964+3G>A in the MYO15A gene) associated with non-syndromic deafness in previous studies[17][18][19][20][21], 7/10 variants were identi ed in this study for the rst time; these included 4 missense variants (p.C1297F and p.K2217E in CDH23, p.G1315R and p.F2861S in MYO15A), 2 frame-shifting (p.Q2749Efs*93 and p.S3474Pfs*43 in MYO15A), and 1 splicing site (c.4875+1G>T in MYO15A). Moreover, c.4875+1G>T at the conserved donor splice site of MYO15A might affect the correct translation of the protein.…”
mentioning
confidence: 97%
“…Hitherto, 61 variants have been reported to be pathogenic or likely pathogenic, of which, 12 are associated with sensorineural hearing loss (http://www.hgmd.cf.ac.uk/ac/). In addition, c.966dupC (p.T323Hfs*19) has also been detected in the probands from consanguineous Iranian families that show profound [17] or moderate [18] sensorineural hearing loss. COL11A2 is considered a "rare gene" responsible for deafness, especially in China.…”
Section: Discussionmentioning
confidence: 98%
“…Consistent with the recessive inheritance, 10 possible causative variants in 3 deafness-related genes (MYO15A, COL11A2, and CDH23) were detected in homozygotes (two families) or compound heterozygotes (four families, Additional le 1). Although the genes previously known to be associated with hearing loss, except for 3 variants (p.T323Hfs*19 in COL11A2, p.3417delS and c.5964+3G>A in the MYO15A gene) associated with non-syndromic deafness in previous studies [17][18][19][20][21], 7/10 variants were identi ed in this study for the rst time; these included 4 missense variants (p.C1297F and p.K2217E in CDH23, p.G1315R and p. conservation prediction showed that the amino acid substitutions were highly conserved across vertebrates. The rst 3 missense variants interrupt the normal protein function, as predicted by the bioinformatic programs (Polyphen2, SIFT, and Mutation Taster).…”
Section: Candidate Pathogenic Variants Identi Ed By Whole-exome Sequementioning
confidence: 98%
“…The EVC , located at chromosome 4p16.2, contains 21 exons and encodes a 992‐amino acid protein (Ruiz‐Perez et al, ; Shi et al, ). It orients head‐to‐head with its homolog gene EVC2 , which also encodes a single‐pass type I transmembrane protein (Vona et al, ). These two proteins interact directly to form a complex at the primary cilium membrane (EvC zone), which is essential for normal endochondral growth and intramembranous ossification (Shi et al, ; Umair et al, ).…”
Section: Discussionmentioning
confidence: 99%